If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -7 = -7 Reorder the terms: -7 + 7x = -7 Add '7' to each side of the equation. -7 + 7 + 7x = -7 + 7 Combine like terms: -7 + 7 = 0 0 + 7x = -7 + 7 7x = -7 + 7 Combine like terms: -7 + 7 = 0 7x = 0 Solving 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '7'. x = 0 Simplifying x = 0
| 12(2x-5)=4(6x+8) | | x^3-3x^2-9x-5=0 | | -15i=4 | | 4(t-6)+6t=5(2t+4)-12 | | 5x^4+35x^3+60x^2=0 | | 9x^2-22x-15=0 | | 6+11p-3=8p+33-3p | | 9x+17=x | | 6(t-2)+6t=6(2t+4)-8 | | 1/-15=4 | | -10x+6y=4 | | -8x+5y=3 | | -2(4s-6)-12=-3(4s+4)-4 | | 6x-10y=-28 | | -1/6(x-12)+1/2(x+2)=x-21 | | 8x-5y=-29 | | 3x-3-3x=4x+11 | | -9x+8y=24 | | 22y=-88 | | -3x+y=3 | | 3(4x+7)=-32+41 | | -1/6(x-18)+1/2(x+2)=x+4 | | -8x+8y=-16 | | 3x^2-11x+12=0 | | 13p=39 | | (x+5)(x-1)+(x-3)(x-1)=(x+1)(x-3) | | -x+6y=-30 | | X^2-13+12=0 | | (2x-9)3=8-3x | | 8(3x-7)=2(12x+3) | | (x-3)(x+2)=(x-4)(x+1)-(x+1)(x+2) | | 25m=-125 |